2019
DOI: 10.7554/elife.42693
|View full text |Cite
|
Sign up to set email alerts
|

Extensive transmission of microbes along the gastrointestinal tract

Abstract: The gastrointestinal tract is abundantly colonized by microbes, yet the translocation of oral species to the intestine is considered a rare aberrant event, and a hallmark of disease. By studying salivary and fecal microbial strain populations of 310 species in 470 individuals from five countries, we found that transmission to, and subsequent colonization of, the large intestine by oral microbes is common and extensive among healthy individuals. We found evidence for a vast majority of oral species to be transf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
320
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(339 citation statements)
references
References 49 publications
16
320
0
3
Order By: Relevance
“…Not coincidentally, the presence of Fusobacterium nucleatum in paired saliva and colon samples of the patients with colorectal cancer has been reported, 2 3 raising interest in whether disease starts in the mouth or in the intestine. [4][5][6] Another reason people are interested in oral microbes is their potentials serving as biomarkers for systemic diseases. 3 7-9 In this study, we examined how long the collapsed bacterial community can recover to its initial state when suffering from disturbance and whether oral microbes have sufficient robustness to serve as biomarkers.…”
Section: Lettermentioning
confidence: 99%
“…Not coincidentally, the presence of Fusobacterium nucleatum in paired saliva and colon samples of the patients with colorectal cancer has been reported, 2 3 raising interest in whether disease starts in the mouth or in the intestine. [4][5][6] Another reason people are interested in oral microbes is their potentials serving as biomarkers for systemic diseases. 3 7-9 In this study, we examined how long the collapsed bacterial community can recover to its initial state when suffering from disturbance and whether oral microbes have sufficient robustness to serve as biomarkers.…”
Section: Lettermentioning
confidence: 99%
“…Subgingival biofilms in individuals with periodontal diseases present continually reservoirs of gramnegative bacteria (Li et al, 2000). It is reported that species associated with periodontitis showed evidence for mouth-togut transmission (Schmidt et al, 2019). Swallowing high doses of periodontal pathogenic microorganisms for a long time might induce dysbiosis of the intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…a ↑↓ arrows indicate increase or decrease in relative abundance, when referring to taxonomic differences. factor that can determine gut composition (Schmidt et al, 2019). The increased presence of lactic acid bacteria in this population and its association with worse clinical, inflammatory, and metabolic profiles is surprising given that lactic acid bacteria are often considered healthpromoting and anti-inflammatory (Ménard et al, 2004).…”
Section: Discussionmentioning
confidence: 99%